Answer:
11
Step-by-step explanation:
<u><em>SUBTRACT</em></u>
Answer:
10x + x^4/x-2
Step-by-step explanation:
Combine like terms
(10x + x^4)/(x-2)
let X be number of students
and y be total cost
when 30 students (30,X)where at the gym it's costs 200 (y,200)
=that is (X,y)=(30,200)
when 70 students where at the gym
=(X,y)= (70,330)
now we find the slope
M=y2-y1/x2-x1
= 330-200/70-30
= 100/40
= 2.5=3
now
Y=Mx+b
Y=2x+b
we need to find the value of b
so,we substrate for X and Y
X=30,200
200=2(30)+b
re-arrange
B+60=200
B=200-60
=140
y=2x+140
For the other questions, I can look at the equation I got. The y-intercept (b value) is $200. That means that we are adding $200 on to the price all the time. That's the price for the empty bus. The 2x means to multiply the number of people by two and add this to the $120. So each person is $2.
hope it's helpful
and please I really need brainliest, thanks
The ratio of the length to the width is
![\rm \dfrac{L}{W}](https://tex.z-dn.net/?f=%5Crm%20%5Cdfrac%7BL%7D%7BW%7D)
.
The ratio of the sides will be the same for the scale and actual figures.
![\rm \dfrac{2.4}{3.6}=\dfrac{27}{W}](https://tex.z-dn.net/?f=%5Crm%20%5Cdfrac%7B2.4%7D%7B3.6%7D%3D%5Cdfrac%7B27%7D%7BW%7D)
I took the L/W of the scale figure
and set it equal to the L/W of the actual figure.
Now we can solve for the unknown width.
Cross-multiplication gives us this,
![\rm 2.4W=3.6\cdot27](https://tex.z-dn.net/?f=%5Crm%202.4W%3D3.6%5Ccdot27)
Divide by 2.4 and simplify,
![\rm W=40.5](https://tex.z-dn.net/?f=%5Crm%20W%3D40.5)
Hope that helps! :)
Step-by-step explanation:
that is
sum(2^r) for r=1 to n, plus sum(1/2) for r=1 to n.
and that is
sum(2^r) + n/2 for r=1 to n.
2^r is a geometric sequence with 2 being the common ratio (every new term is created by multiplying the previous term by 2).
and since r is starting at 1, the first term a1 = 2.
the formula for the sum of a finite geometric sequence is
Sn = a1×(1 - r^n) / (1 - r)
with r being the common ratio .
so, in our case
Sn = 2×(1 - 2^n) / (1 - 2)
Sn = (2 - 2^(n+1)) / -1 = 2^(n+1) - 2
and so, in total we get
2^(n+1) - 2 + n/2 = 2^(n+1) + (n - 4)/2